Investigating the Hydraulic Properties of Unsaturated Crushed Stone Aggregate to Enhance Horizontal Drainage Systems on Soft Ground - Seongyoon Lim; Myeonghwan Kim (Advances in Civil Engineering)
Crushed stone aggregate materials are commonly used for basal embankment support on soft subgrades or for horizontal drainage in soft soils. When the drainage material is constrained by earth pressure and water pressure, it changes to an unsaturated water-permeable state. If the pore water pressure decreases as the compaction of the soft ground increases, the water does not drain through the drainage material. Therefore, it is necessary to measure the critical pressure value (air entry value) going from saturation to desaturation. That is, even if the pore water pressure is small, the water must be discharged through the drainage material. Therefore, this study presents experimental results for gravity drainage and soil-water retention curves (SWRCs) using mixed crushed stone aggregate samples at different particle size distributions and different compaction conditions. SWRC experiments indicate that porosity, hydraulic conductivity under saturated conditions, and air entrapment decrease with increasing sand content. Also, the samples retained more water at higher suction values, although the porosity decreased with increasing sand content. This phenomenon is due to the tendency of the uniformity coefficient to increase as more fine particles are added to the crushed stone aggregate. In addition, it is considered that the function as a drainage material is possible only when it shows a higher air entry value than that of the loose crushed stone aggregate drainage material. Therefore, for drainage materials using crushed stone aggregate, analysis of the soil-water retention curve for unsaturated soil should be preceded.